Cryptography and coding : 17th IMA International Conference, IMACC 2019, Oxford, UK, December 16-18, 2019, proceedings /: 17th IMA International Conference, IMACC 2019, Oxford, UK, December 16-18, 2019, proceedings. (2019) - Unknown
No abstract available